The Effect Of Product Quality, Distribution Channels And Service Quality Towards The Satisfaction Of Customer Purchase Of Roma Biscuit Store In PT. Inbisco Niagatama: The Effect Of Product Quality, Distribution Channels And Service Quality Towards The Satisfaction Of Customer Purchase Of Roma Biscuit Store In PT. Inbisco Niagatama - Sufika Sary; Ricky Ricky; Gilbert Gilbert; Steven Chuandra (Jurnal Mantik, 2020)
The purpose of this study is to discuss product quality, distribution channels, and service quality on customer purchase satisfaction buying biscuit products at PT Inbisco Niagatama. The decline in Roman biscuit customer satisfaction can be seen from the failure to achieve sales targets that cause product quality to decrease, channel distribution which is increasingly difficult and service quality to be less satisfactory. The population rose by 194 customers and the sample in this study was released 131 customers. The research method uses multiple linear regression analysis techniques. Hypothesis testing results partially obtained value of t> t table or 3.559> 1.979 with a significant value of 0.001 <0.05. Hypothesis testing results partially obtained value of t> t table or 2.734> 1.979 with a significant value of 0.007 <0.05. Hypothesis testing results partially obtained value of tcount> ttable or 2.609> 1.979 with a significant value of 0.010 <0.05, then partially product quality, distribution distribution and service quality are very positive and significant impact on satisfaction with the purchase of Roman biscuit products at PT Inbisco Niagatama Results Simultaneous hypothesis testing obtained Fcount (10.438)> Ftable (2.68) and a significance probability of 0.000 <0.05 namely product quality, distribution channels, and land quality, which is positive and significant for the purchase of Roman biscuit products at PT Inbisco Niagatama . The coefficient of determination test results obtained adjusted R Square value of 0.179, this means 17.9% of the variation of the dependent variable that can be approved by variations of variables that are not discussed in this study, such as promotions, prices, brand image and so on.